A novel evaluation method for in situ space debris detection based on conductive traces - Fexer, Sebastian (Frontiers in Space Technologies, 2022)
To enable the detection of micrometeorids and small-sized space debris (MMSD) in the (sub)-mm range, in-situ detectors aboard a spacecraft are the tool of choice. Unfortunately only a few projects have been sent to space until today. However, knowledge of the MMSD population is important to keep the reference models up-to-date and gain more insight into factors like the amount of debris and its distribution along certain orbits. This will be crucial for the safety of current and future spaceflight missions. Present-day in-situ detection systems mostly rely on impact recognition and characterization using different methods. One of them is the perforation of a special detection area during such an event. These areas consist of one or more layers provided with conductive traces. Any interruption of one of these lines can be recognized using some kind of electrical continuity testing method or the determination of the resistance. This goes along with some drawbacks, like the difficult or even impossible multi-event recognition along one line. The proposed concept relies on a reflectometric approach. In doing so, e.g. pulses are being sent along a well-defined transmission line, which is a part of the detection area. Any alteration of the characteristic line impedance, for instance due to an impact, will generate reflections back into the generator. Their evaluation can provide the location as well as the complex impedance of the perturbation.